1983
DOI: 10.2514/3.44849
|View full text |Cite
|
Sign up to set email alerts
|

Strut or guide vane secondary flows and their effect on turbomachinery noise

Abstract: Results of an investigation in which the turbomachinery rotor sound spectra were correlated with aerodynamic measurements of upstream strut secondary flow are reported. The aerodynamic measurements, carried out in an aeroacoustic turbomachinery facility, included mean-velocity and turbulence-intensity profiles across the wake and the secondary flow regions at the strut exit or rotor inlet. The measurements were carried out at incidence angles of 0, 4, 12, and -12 deg to the strut. The far-field acoustic measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In a study on the aerodynamic noise of the propeller fan, the authors verified experimentally the mechanism of the discrete frequency noise of a propeller fan generated because of the pseudo rotor-stator interaction [4]. In such previous studies, there are not a few study cases about the mechanism of the discrete frequency noise synchronizing with the blade passing frequency of the high specific speed fan [5]. On the other hand, in a study on the turbulent noise of a low pressure axial fan, Fukano et al suggested that the broadband noise was mainly generated because of the vortex shedding to the wake if the turbulence of the incoming flow to the fan is weak [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the aerodynamic noise of the propeller fan, the authors verified experimentally the mechanism of the discrete frequency noise of a propeller fan generated because of the pseudo rotor-stator interaction [4]. In such previous studies, there are not a few study cases about the mechanism of the discrete frequency noise synchronizing with the blade passing frequency of the high specific speed fan [5]. On the other hand, in a study on the turbulent noise of a low pressure axial fan, Fukano et al suggested that the broadband noise was mainly generated because of the vortex shedding to the wake if the turbulence of the incoming flow to the fan is weak [6].…”
Section: Introductionmentioning
confidence: 99%
“…In such previous studies, there are not a few study cases about the mechanism of the discrete frequency noise synchronizing with the blade passing frequency of the high specific speed fan [5]. On the other hand, in a study on the turbulent noise of a low pressure axial fan, Fukano et al suggested that the broadband noise was mainly generated because of the vortex shedding to the wake if the turbulence of the incoming flow to the fan is weak [6]. Whereas the relationship between the tip vortex and noise has been discussed in a study of the aerodynamic noise from the propeller fan [7], there are several reports stating that the affect of the tip vortex on the fan noise is small in the vicinity of the design point [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the interactions between rotor and stator may induce unnecessary aeroacoustic noise if the guide vanes are poorly designed. The mechanism of rotor-stator interaction noise was investigated by Lakshminarayana et al (1982). He suggested that the main source of this noise was caused by flow irregularities in the tip leakage flow and the secondary flow around the tip and hub regions.…”
Section: Introductionmentioning
confidence: 99%